Efficient Computation of Green's Functions for Lossy Uniaxial Anisotropic Layered Media - Li, Dawei; Wilton, Donald R.; Jackson, David R.; Chen, Ji; Wang, Hanming (Radio science, 2019)
The efficient computation of Green's functions for uniaxial anisotropic layered media is investigated. Both field and mixed‐potential layered medium Green's functions (LMGFs) are discussed for different applications. An asymptotic subtraction (singularity extraction) and the weighted average method are combined for the acceleration of LMGF computation. A full collection of Sommerfeld and related identities used in the acceleration is summarized and generalized to uniaxial anisotropic medium for both field and mixed‐potential LMGFs. When lossy media are considered, the effective distance from the source to the observation point becomes a complex number depending on the anisotropic ratio of the horizontal to vertical media parameters. In addition, the evaluation of half‐line source potentials, which are introduced to accelerate the scalar potential correction term for vertical currents, is generalized to the complex domain by analytic continuation. Several numerical examples are used to demonstrate the efficiency and accuracy of the resulting algorithms. Key Points This paper computes Green's functions efficiently in lossy uniaxial anisotropic layered media A full collection of Sommerfeld and related identities is summarized and generalized to lossy uniaxial anisotropic medium